Taboo in Sasak Community - Ayub Ayub (Universitas Pendidikan Ganesha, 2012)
This paper discusses about taboo in Sasak. The question answered is `How is the classification of taboo in Sasak? ` The purpose of this study is to describe the classification of taboo in Sasak used by Sasak people. The methods used in this study were note-taking, recording, in-depth interviewing, and observation. The method used in analyzing data is descriptive-qualitative method. After the data were collected, they were identified and classified, then analyzed as well as described based on their classification. The result of the research is that taboo in Sasak can be categorized into dietary restriction, sexual intercourse, nicknaming, mentioning certain animals, shouting `antih aku`, saying `sial`, mentioning certain diseases, taking the oath, and pointing towards something and giving or taking something using left hand. From that classification, taboo can be based on religion concept, custom or traditional myth or belief, and moral judgment of Sasak people. Finally, the existence of taboo in Sasak community can be beneficial for the people of Sasak in that they can be free from calamity by avoiding certain things considered to be bad thing to do.